2018
DOI: 10.12659/msm.906451
|View full text |Cite
|
Sign up to set email alerts
|

Game-Based Virtual Reality Canoe Paddling Training to Improve Postural Balance and Upper Extremity Function: A Preliminary Randomized Controlled Study of 30 Patients with Subacute Stroke

Abstract: BackgroundVirtual reality (VR) training with motion-controlled console games can be incorporated into stroke rehabilitation programs. The use of a variety of gaming software can provide the patient with an opportunity to perform activities that are exciting, entertaining, and that may not be feasible in clinical environments. The aim of this preliminary randomized controlled study was to investigate the effects of game-based VR canoe paddling training, when combined with conventional physical rehabilitation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 28 publications
(30 reference statements)
1
44
0
7
Order By: Relevance
“…However, the remaining studies used the terms “virtual reality intervention” and “game-based intervention” interchangeably. For instance, their treatment protocols incorporated the use of different gaming-based engines or systems, such as the Xbox Kinect system ( 45 , 52 ), Unity 3D game engine ( 22 ), Nintendo Wii Sports Resort package ( 12 , 21 , 23 , 47 , 53 ), the YouGrabber system ( 56 ), Jintronix Rehabilitation system ( 49 ), and PlayStation console ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the remaining studies used the terms “virtual reality intervention” and “game-based intervention” interchangeably. For instance, their treatment protocols incorporated the use of different gaming-based engines or systems, such as the Xbox Kinect system ( 45 , 52 ), Unity 3D game engine ( 22 ), Nintendo Wii Sports Resort package ( 12 , 21 , 23 , 47 , 53 ), the YouGrabber system ( 56 ), Jintronix Rehabilitation system ( 49 ), and PlayStation console ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…That being said, the number of studies investigating the effect of VR-based interventions in patients with subacute stroke remains scarce (9,(21)(22)(23), and no conclusions have been reached in this regard. This topic is of great interest because (1) the plasticity of the brain remains good during the acute and subacute phase (24,25) and (2) the effectiveness of rehabilitation therapy-induced neuroplasticity is limited in chronic stroke patients, particularly those who missed the window of opportunity that is present during the subacute phase (when the brain plasticity peaks) (26).…”
Section: Introductionmentioning
confidence: 99%
“…When adding immersive technologies to the equation, VR-based rehabilitation has shown to have the following documented advantages; increased repetitions over the proposed exercises and augmented patient engagement; the capacity to track the patient's recovery process over time; possibility of requiring low clinical supervision, which indeed eases home use and tele-rehabilitation; and enhanced motor (re)learning by different types of stimuli (visual, auditory or haptics) [10,28,36]. Nevertheless, playing SGs has also shown to be crucial in stimulating the development of basic learning skills, such as paying attention, promoting visual-motor coordination, improving logical spatial reasoning and orientation, among others [37,38].…”
Section: Advantages Of Virtual Reality and Game-based Therapiesmentioning
confidence: 99%
“…WBV is able to improve results of the Functional Reach Test and the Timed Up and Go (TUG) test, which have a positive effect on the balance and gait function of patients who had a stroke 20. Results of an RCT concluded that VR is an effective rehabilitation therapy which can improve postural balance and upper extremity function in patients who had a stroke 21. Exercises such as bilateral upper extremity exercises,22 step climbing exercise23 and trampoline training24 are beneficial to the ability to balance and for fall prevention.…”
Section: Introductionmentioning
confidence: 99%